Repensando o processo decisório colegiado do Supremo Tribunal Federal : uma crítica ao desenho deliberativo e ao modelo seriatim - Vieira, Isabelle Almeida (2021)
The main functions of the Brazilian Supreme Federal Court (STF) are the exercise of judicial review and the formation of precedents on constitutional issues. However, its collegiate decision-making process is not the most appropriate for the exercise of its institutional mission, given the deliberative deficit among the justices and the use of the seriatim (aggregative) decision-making model, which, among other factors, makes it difficult to identify the ratio decidendi and does not contribute to the formation of a precedent culture. From this point of view, supported by elements of the deliberative democracy theory, it seeks to demonstrate that the institutional design and customary practices adopted by constitutional courts can directly affect their deliberative performance, thus compromising their democratic legitimacy, since the more deliberative a court is, the greater its legitimacy will be. Therefore, it will be essential, through analysis in the field of comparative law, to examine the decision-making models adopted by constitutional courts around the world, such as per curiam, seriatim and majoritarian practice, in order to assess what positive points can be taken from these models and incorporated into the brazilian reality by improving some institutional aspects of the STF's collegiate decision-making process. As suggestions, some guidelines to be followed are mentioned: the fixing of legal summaries as an intermediate way to the formation of a precedent culture; the maximization of previous and internal deliberation; the improvement of the report and the rapporteur’s vote draft; the establishment of secret meetings; a two-phase virtual plenary session; the adoption of the voting model issue-by-issue; as well as the decision in a single text format with the possibility of dissenting opinions in separate.